Substance abuse : prevention & treatment - Avraham, Regina (Encyclopedia of psychoactive drugs., 1988)
Examines the drug problem, why legal efforts to prevent drugs from reaching the public have failed, and steps the government has taken to enter the fields of prevention and treatment.